Financing instrument for risks managing. Polish experience - Przybytniowski, Jarosław W. (Business: Theory and Practice, 2013)
The study is the result of scientific research carried out in co-operation with the European Business Club. Tke issue presented in eariler study and it is a continuation of the research conducted among companies which use insurance as an instrument of financing ecological risks. The structure of the study has been subordinated to the thesis according to which insurance can be an important instrument for financing ecological risks, including risks in mining. According to the subject of discussion, the following were applied: elemental analysis – if the object of study requires the distribution of the elements without looking for mutual dependence between them; casual analysis – when there was a need of looking for the cause–effect relationships between the elements of the object of the study; logical analysis – consisting of breaking down the object of study, taking into account the existing one in logical relations.